Dietary Sodium Intake and Health Indicators: A Systematic Review of Published Literature between January 2015 and December 2019 - Overwyk, Katherine J (Adv Nutr, 2020)
As the science surrounding population sodium reduction evolves, monitoring and evaluating new studies on intake and health can help increase our understanding of the associated benefits and risks. Here we describe a systematic review of recent studies on sodium intake and health, examine the risk of bias (ROB) of selected studies, and provide direction for future research. Seven online databases were searched monthly from January 2015 to December 2019. We selected human studies that met specified population, intervention, comparison, outcome, time, setting/study design (PICOTS) criteria and abstracted attributes related to the study population, design, intervention, exposure, and outcomes, and evaluated ROB for the subset of studies on sodium intake and cardiovascular disease risks or indicators. Of 41,601 abstracts reviewed, 231 studies were identified that met the PICOTS criteria and ROB was assessed for 54 studies. One hundred and fifty-seven (68%) studies were observational and 161 (70%) focused on the general population. Five types of sodium interventions and a variety of urinary and dietary measurement methods were used to establish and quantify sodium intake. Five observational studies used multiple 24-h urine collections to assess sodium intake. Evidence mainly focused on cardiovascular-related indicators (48%) but encompassed an assortment of outcomes. Studies varied in ROB domains and 87% of studies evaluated were missing information on ≥1 domains. Two or more studies on each of 12 outcomes (e.g., cognition) not previously included in systematic reviews and 9 new studies at low ROB suggest the need for ongoing or updated systematic reviews of evidence on sodium intake and health. Summarizing evidence from assessments on sodium and health outcomes was limited by the various methods used to measure sodium intake and outcomes, as well as lack of details related to study design and conduct. In line with research recommendations identified by the National Academies of Science, future research is needed to identify and standardize methods for measuring sodium intake.